The Transportation of Bigamists in Early-Nineteenth-Century England and Wales. Issue 3 (2nd September 2019) - Probert, Rebecca; D'Arcy-Brown, Liam
ABSTRACT: Between 1795 and 1853, over 250 men and women were sentenced to transportation for committing the crime of bigamy. This harsh treatment is at odds with the assumption that the sentences handed down to bigamists were generally light. This article provides the first in-depth study of the use of transportation in this context, drawing on the criminal registers, the Proceedings of the Old Bailey, and local and national newspaper reports in order to ascertain who was transported for bigamy, and why. Analysing a range of aggravating and mitigating factors, it shows why certain cases were deemed to merit the harshest form of punishment, while others, despite exhibiting some of the same factors, were treated more leniently. The sheer greed, deceit and nastiness demonstrated by many of these bigamists provide a significant counter-narrative to the depiction of bigamy as a substitute for divorce and raises broader questions about its incidence.